Ensaios de adubação química do cafeeiro (Coffea arabica L.) em duas localidades da "Zona da Mata" de Minas Gerais - Oliveira Begazo, José Carlos Enrique (Revista Ceres, 2025)
The work was started in 1961 with the objetive to study the effect of fertilization in the performance of coffee consider- ing production, fruit maturity at harvest and rate of drying of the top branches.